PENGARUH TERAPI MUROTTAL AL-QUR’AN TERHADAP PENURUNAN SKALA NYERI PADA PASIEN CEDERA KEPALA DI RUANG BEDAH UMUM RSUD ULIN BANJARMASIN - Noor Khalilati; Muhammad Humaidi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
Head injury is one of the main causes of death and disability, so far pharmacologic treatment is used to treat the pain. The researcher tried to provide treatment with listening to murottal Al-Qur'an therapy so that was able to reduce pain due to head injury. The aim was to determine the effect of listening to murottal Al-Qur'an therapy on the reduction in pain scale of head injury patients in the operating room of Ulin Hospital of Banjarmasin. The design was Quasy_Experimental with One Group Pretest-Postest. The population were all patients of head injury in operating room and the sampling technique used purposive sampling. The instrument used a questionnaire sheet. The measurement of the Numerical Rating Scale (NRS) used univariate analysis and bivariate analysis with the Paired T-Test. The level of moderate pain scale before listening mostly amounted to 15 (100%) people, after doing therapy there were 13 (86.7%) people with mild pain. There was an influence of listening to murottal Al-Qur'an on the reduction of the pain scale of head injury patients in operating room. The hypothesis is accepted at the significance level of 0.000 <0.05. The results of this paper are expected to provide information to patients in reducing pain’s response. Keyword: Head Injury Patient, Murottal Al-Qur’an, Pain Scale